Gains and losses-a decade of China/Unicef cooperation in service teacher training - Liu, Jian (KDI School, 1999)
As the world becomes increasingly globalized, there have been more and more co-operative programs between countries and organizations. But it is common that some of these international cooperative projects have eventually turned out to be unsuccessful. What are the reasons? This paper argues that an equal partnership between cooperators is, if not the most, one of the crucially important elements to achieve positive outcomes, through a case study of China/UNICEF co-operation in in-service teacher training (ISTT) project implemented in the People’s Republic of China, from 1982 up to the present. It addresses the issue of gains and losses entailed in this project, examines the overall partnership between China and UNICEF and its effects on project characteristics and interactions, success and development and conclude that once partnership between donor and recipient in aid relationship is more equal, their cooperation could be more constructive and productive. This should be the final goal of aid in its historical mission Taking the ISTT project as a case-study of co-operation between China and UNICEF, this study represents an in-depth reflection on my close observation, grounded by analysis of project documents, implementation processes and interview data of six project actors from both Chinese and UNICEF sides. UNICEF assistance can provide vital educational inputs in terms of both ideas and funds, particularly when fully supported by strong internal inputs in the same terms and the overall educational policy. A large developing nation-state like China, its extensive partnership with UNICEF is a unique occurrence, but is one that has an exemplary role and impact for other developing countries The challenge to international aid provision is that development is ultimately the responsibility of recipients. Any type of initiative for change and improvement must come from the commitments, thoughts and efforts of the recipient itself. Only after these happen can the recipient ultimately become independent of aid
Thesis(Master) --KDI School:Master of International Relations and Political Economy,1999